Analisis Komparatif Kinerja Keuangan Berbasis Perilaku Pembayaran Deviden - Yusuf, Ikraami s (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The results of the study: show that there are differences in financial performance based on the behavior of dividend payments with a stable and unstable category in the Food and Beverage Company on the Indonesia Stock Exchange. Hypothesis testing in this study 0.01 <0.05 or Sig (2-Tailed) means that there is a difference in the company's financial performance with stable and unstable dividend behavior. So in general there are differences in financial performance aspects of Net Profit Margin (NPM) and Return on Equity (ROE), Return On Investment (ROI), Current Ratio, Total Asset Turn Over (TATO) and Debt to Asset Ratio (DAR) dividend payment categories stable and unstable at food and beverage companies that went public on the Indonesia Stock Exchange.Keywords: Financial Performance, Dividend Payment Behavior